Application of Ornaments Using Decoupage Technique Combined with the effect of acrylic paint on furniture At UD Mandiri Telaga Jaya (Global Scientific Review, 2023)
his research aims to apply ornaments using decoupage techniques to furniture at UD Mandiri Telaga Jaya. The type of research is R&D (research and development/) research with a qualitative approach . Data collection: observation, interviews, experiments, documentation. Data analysis: data reduction, data presentation, and verification. Research results: stages of applying ornaments using decoupage techniques to furniture: 1) analysis of potential, problems, and gathering information: a) strategic location; b) supporting transportation; c) woodpile; d) adequate buildings; e) building shop. All potential becomes UD Mandiri's strength in facing competitors. The next problem with UD Mandiri is that consumers' tastes for furniture with additional ornaments have not been met; 2) product design : the product uses drawers and chairs that are already available. The design process is used to determine tissue and napkin motifs and create designs for arranging furniture motifs; 3) design validation; 4) design improvements: adding ornamental motifs using painting techniques; 5) product trials; a) preparation of tools and materials; b) preparation of furniture; c) application of napkin wipes; d) adding ornaments to the edges of furniture using painting techniques using acrylic paint; e) applying varnish; f) research results . The application of tissue paper napkins using decoupage techniques as ornaments on furniture, chairs and drawers, has added to the aesthetic value of the furniture , making it an alternative for developing furniture ornaments at UD Mandiri Telaga Jaya